Anionic phospholipid interactions with the potassium channel KcsA: simulation studies. - Deol, S; Domene, C; Bond, P; Sansom, MS (2006)
Molecular dynamics (MD) simulations have been used to unmask details of specific interactions of anionic phospholipids with intersubunit binding sites on the surface of the bacterial potassium channel KcsA. Crystallographic data on a diacyl glycerol fragment at this site were used to model phosphatidylethanolamine (PE), or phosphatidylglycerol (PG), or phosphatidic acid (PA) at the intersubunit binding sites. Each of these models of a KcsA-lipid complex was embedded in phosphatidyl choline bilayer and explored in a 20 ns MD simulation. H-bond analysis revealed that in terms of lipid-protein interactions PA > PG >> PE and revealed how anionic lipids (PG and PA) bind to a site provided by two key arginine residues (R(64) and R(89)) at the interface between adjacent subunits. A 27 ns simulation was performed in which KcsA (without any lipids initially modeled at the R(64)/R(89) sites) was embedded in a PE/PG bilayer. There was a progressive specific increase over the course of the simulation in the number of H-bonds of PG with KcsA. Furthermore, two specific PG binding events at R(64)/R(89) sites were observed. The phosphate oxygen atoms of bound PG formed H-bonds to the guanidinium group of R(89), whereas the terminal glycerol H-bonded to R(64). Overall, this study suggests that simulations can help identify and characterize sites for specific lipid interactions on a membrane protein surface.